Predictors of Readiness for Mobility Transition in Older Drivers. Issue 2 (17th February 2018) - Kandasamy, Deepika; Harmon, Annie C.; Meuser, Thomas M.; Carr, David B.; Betz, Marian E.
ABSTRACT: We administered the Assessment of Readiness for Mobility Transition (ARMT) to 301 older drivers and compared total scores with participant characteristics. Overall, 18% of participants were not attitudinally ready for mobility transition, while 19% were very ready. Notably, participants with hospitalizations in the past year were either very ready for mobility transition (20% vs 14% without hospitalizations) or not ready at all (30% vs 17%). Significant health events may polarize reactions towards mobility transition. Individualizing communication about driving cessation readiness could help address such differing views. To further consider its effectiveness, ARMT could be utilized in mobility transition counseling interventions.